COMPLICATIONS NASOGASTRIC TUBE INSERTION AND TREATMENT - Dwi Kresnawati (Universitas Udayana, 2013)
Insertion of a nasogastric tube (NGT) is an invasive procedure that is often done by increasing medical emergency. There are two indications of this procedure,the indications are for diagnostic and therapeutic interest mainly to access and evaluate the nutritional content of the stomach for patients with suspected gastrointestinal bleeding. Although nasogastric tube insertion simpler, easier and safer than with a pipe orogastrik, but complications can occur during installation such as malposition of NGT, epistaxis, mucosal trauma, aspiration pneumonia, hypoxemia and pneumothorak. So the importance of knowledge, skills, and how treatment for complications arising prevents one way to ensure the proper placement of NGT.